Identifying symptom subgroups in patients with ME/CFS – relationships to functioning and quality of life. Issue 1 (2nd January 2017) - Jonsjö, Martin A.; Wicksell, Rikard K.; Holmström, Linda; Andreasson, Anna; Bileviciute-Ljungar, Indre; Olsson, Gunnar L.
ABSTRACT: Background: It is still not clear whether the diagnosis Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) constitutes one single disease entity, as diagnosis depends on clinical case definitions. The variation of symptoms across individuals indicates important differences between individuals diagnosed with ME/CFS. Also, the variation in daily functioning and quality of life measures among subgroups of symptoms is still unclear. Purpose: The present study examines the associations between symptoms in ME/CFS, and evaluates the relationships between symptom subgroups, functioning and quality of life. Methods: Data were collected from 106 adults as part of the assessment at a tertiary specialist clinic for ME/CFS. Principal component analyses (PCA) were utilized to identify symptom subgroups, and the relationships with functioning and quality of life were evaluated using bivariate correlations. Results: The PCA suggested four statistically distinct and clinically meaningful subgroups of symptoms. The latent constructs were labeled Inflammatory, Pain, Neurocognitive, and Autonomic. All symptom subgroups correlated significantly with measures of fatigue, mood, functioning and quality of life. Notably, the correlations between symptom subgroups and criteria variables (e.g. mood) varied in strength, indicating a difference in the relative importance of symptom subgroups. Conclusions: Although tentative, the results from this study support previous research and suggest that there are important symptom subgroups among individuals with ME/CFS. Furthermore, these results indicate that symptom profiles may be of importance to understand the variation between individuals in the impact of symptoms on functioning. Thus, more research is warranted to validate these findings and investigate possible differences in etiology between patient subgroups.